Development of Appsmart Based on Self-Directed Learning with Articulate Storyline for Drama Scripts - Saragih, M Afiv Toni Suhendra; Winarti, Winarti; Izar, Sri Listiana; Hasibuan, Akhirunnisa (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This Research aims to develop and test the effectiveness of the Appsmart learning application, based on the Self-Directed Learning (SDL) model supported by Articulate Storyline, for drama script learning in the Indonesian Language and Literature Education Study Program at Universitas Muhammadiyah Sumatera Utara. The Research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The Research subjects are fourth-semester students enrolled in a Drama course. The Research instruments include expert validation sheets, user response questionnaires, comprehension tests, writing skill assessment rubrics, observations, and interviews. The Research results show that the Appsmart application received a